Ataques ao trabalho docente na pandemia da Covid-19: artefatos midiáticos, currículo e pedagogia cultural em Mato Grosso do Sul - OTAVIO HENRIQUE RODRIGUES DOS SANTOS (2023)
This research aims to analyze the curriculum and cultural pedagogy of part of the digital media artifacts that produce attacks against teaching work during the Covid-19 pandemic in Mato Grosso do Sul contexts. The Covid-19 pandemic caused schools to close their gates, thus making classes in the emergency remote teaching format. During this period, numerous educational difficulties were faced, both by students and teachers. This is an online ethnographic method study, having as a research field the artifacts present in digital media, through Facebook newspaper pages and a YouTube channel. With this, three newspapers were selected for content analysis that dealt with teaching work in the pandemic, and from these newspapers, 18 news items were chosen in all. In addition, a governmental YouTube page that offered training to teachers in a municipal education network was also analyzed. In the introduction there is a brief report on the pandemic and the difficulties faced by teachers, and a discussion on the perspective used as references in this research, the post-critical in education. In the second chapter there is a production survey and a discussion about the works found. In this chapter I also bring the methodological process, the artifacts, the research phases, the bricolage. Finally, in the last chapter I discuss the data found in a centralized look at the curricular-pedagogical process that produced attacks on teaching work. It is concluded that during the pandemic teachers suffered numerous attacks with various speeches. Attacks with hate speech, incitement to violence against the category, attacks with sexual and political speeches, as well as the silencing of the right to express their opinions were found.